Korupsi dan Kemiskinan Dalam Bingkai Pancasila - dan Abd. Kholiq, Shofiyah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2019)
In Indonesia, the practice of corruption is no longer recognizable, meaning that this practice has been carried out by anyone from various groups both working in the private and public sectors, ranging from low-ranking employees to the highest among government and high-ranking State officials. Even it is a social pathology (social disease) that has threatened the life of society, nation and state. Corruption is a reflection of the low morale of the perpetrators so that what appears to be greediness. Whether it is realized or not, corruption is very detrimental to the State even results in poverty. This is contrary to the values ​​of Pancasila which are the life guidelines of the Indonesian people.